Utilization of Islamic Fintech with a Crowdfunding Method to Optimize Zakat Fund Collection - Alya Fadila Hilman, Naila; Maman Pathulrohman, Dede; Siska Sintia Muhtari, Pricila; Fauziah, Raihani; Ghifary Alba Wahyudi, Araya (UIN Sunan Gunung Djati Bandung, 2025)
This research aims to provide an alternative to collecting zakat funds by utilising a digital platform that facilitates the community in terms of distribution and collection of funds. Optimising the use of zakat funds can solve social challenges such as poverty and income inequality. This research uses qualitative methods to analyse the factors and barriers in zakat payment from various sources, with the aim of understanding more deeply about the optimisation of zakat fund collection by considering the problems faced by the community. This research found that the financial technology system with crowdfunding method is able to optimise the collection and distribution of funds that allow individuals or groups to contribute funds collectively, in this case zakat. The cooperation between financial technology platform providers and Lembaga Amil Zakat (LAZ) has enabled muzaki to pay zakat flexibly, through transfer payment and selection of trusted amil, using only internet access. This method will expand the reach of zakat fund recipients and collectors. Although this payment model has started to be used by Badan Amil Zakat Nasional (BAZNAS) and Islamic banks, it has not been fully optimised in Indonesia. The main challenges include uneven accessibility for all levels of society and limited digital literacy.